2018
DOI: 10.1111/jam.14090
|View full text |Cite
|
Sign up to set email alerts
|

Identification of common virulence factors present in enterotoxigenicEscherichia coliisolated from diarrhoeal patients in Kolkata, India

Abstract: Prevalence of ETEC virulence factors would help in tracking ETEC globally and suggests the need of a multivalent ETEC vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
3
6
0
Order By: Relevance
“…The third prevalent pathotype of this study was ETEC causing moderate-to-severe diarrhea in human. The pro les st/lt and st were the most common toxigenic genotype among ETECs, which agrees with Bhakat et al (2019) [30]. None of the strains carried the lt gene alone, which is in contrast with the global prevalence of the gene where the presence of lt is higher than st or st/lt pro le [31].…”
Section: Discussionsupporting
confidence: 88%
“…The third prevalent pathotype of this study was ETEC causing moderate-to-severe diarrhea in human. The pro les st/lt and st were the most common toxigenic genotype among ETECs, which agrees with Bhakat et al (2019) [30]. None of the strains carried the lt gene alone, which is in contrast with the global prevalence of the gene where the presence of lt is higher than st or st/lt pro le [31].…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with our findings, a study on the ETEC population in Nepal revealed that CS21 (62.6%) and CS6 (30.2%) were the most prevalent CFs (Margulieux et al, 2018). Another study in our laboratory earlier detected CS21 as the prevalent CF followed by CS6 among clinical ETEC isolates from Kolkata (Bhakat et al, 2018). In Bangladesh, frequently detected CFs were CS5, CS6 and CS1 (Begum et al, 2014).…”
Section: Discussionmentioning
confidence: 79%
“…The four genes were selected out of many genes reported because of high occurance of these genes in the dirrheagenic E.coli isolates. Recently, the isolates having elt and est genes in dirrheagenic E.coli isolates bore the prevalence of 86% (Bhakat et al, 2019) in India. The shiga like toxin was selected because these are one of the most potent toxin produced by E.coli that causes haemolytic diarrhea or Haemolytic Uremic Syndrome (HUS) in humans.…”
Section: Resultsmentioning
confidence: 99%